2002
DOI: 10.1007/s00417-002-0458-y
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual variability of learning in stereoacuity

Abstract: The great interindividual variability of learning in stereoacuity has important implications for therapeutic tests that use stereoacuity as an outcome measure: To distinguish therapeutic effects from improvements due to repeated testing, each subject's individual learning behaviour has to be taken into account, for example by starting out with an adequate training phase. The number of test repetitions required to reach a fairly constant level appears to be similar among individuals: in our paradigm most of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
3
12
0
2
Order By: Relevance
“…The behavioral component identified by the factor analysis (i.e., PC1) combined aspects of initial performance (i.e., predisposition), the rate of performance improvement, and the quantity of practice required to reach criterion. Our observers were highly variable in their initial performance, a finding concordant with previous studies of complex visual tasks (1) as well as perceptual learning (2)(3)(4)6). Interestingly, task fitness was positively correlated with initial performance, and negatively correlated with the rate of learning and the number of blocks to criterion.…”
Section: Discussionsupporting
confidence: 89%
“…The behavioral component identified by the factor analysis (i.e., PC1) combined aspects of initial performance (i.e., predisposition), the rate of performance improvement, and the quantity of practice required to reach criterion. Our observers were highly variable in their initial performance, a finding concordant with previous studies of complex visual tasks (1) as well as perceptual learning (2)(3)(4)6). Interestingly, task fitness was positively correlated with initial performance, and negatively correlated with the rate of learning and the number of blocks to criterion.…”
Section: Discussionsupporting
confidence: 89%
“…These values are 3168 ± 384 for the sparse stereograms and 3771 ± 795 for the dense stereograms, which are consistent with other studies of perceptual learning of depth discrimination using RDSs (Gantz, Chung & Harwerth, 2007a, Westheimer, 2001). The high variability obtained in the group data for the critical number of training trials (see also the individual functions shown in Figure 2) is consistent with the large inter-individual variability of perceptual learning that is reported by others (Schmitt, Kromeier, Bach & Kommerell, 2002). …”
Section: Resultssupporting
confidence: 90%
“…Several studies have reported considerable intersubject variability in both the occurrence and magnitude of perceptual learning (Fahle et al, 1995; Fahle & Henke-Fahle, 1996; Mukai et al, 2007; Schmitt, Kromeier, Bach, & Kommerell, 2002). Attention has been implicated in both psychophysical and electrophysiological studies as playing a key role in explaining this variability (Ahissar & Hochstein, 1993; Crist, Li, & Gilbert, 2001; Fahle, 2004; Li, Piech, & Gilbert, 2004; Shiu & Pashler, 1992).…”
Section: Introductionmentioning
confidence: 99%